Evaluation the inhibitory efficacy of the Lichen Evernia prunastri extracts against the plant pathogenic fungus Alternaria alternata (Latakia University Journal -Biological Sciences Series, 2020)
This research was carried out to evaluate the inhibitory effect of acetonic, ethanolic, and chloroformic  extracts of Evernia prunastri lichen with concentrations of (25, 50, 75, 100) mg/ml  against the  plant  pathogenic fungus  Alternaria alternata. , all  extracts showed a clear inhibitory effect  on the growth of fungal hyphae and spores germination of the studied species compared to the control.Acetonic extract showed  a high inhibition effect on (100) mg / ml growth of fungal hyphae and spores germination by (100) %   respectively compared to the control, followed by ethanolic extract, the inhibiton rates at the same concentration were (92.96)%  for the growth of fungal hyphae and  (100)%  for inhibition of spores germination. While the chloroformic  extract had the least effective it compared to the previous tow extracts when the concentration (100) mg / ml, the inhibitory ratio for fungal hyphae reached (67.04)% and (77.30)% for spores germination.The results of this study confirm that  Evernia prunastri  lichen extracts, especially acetonic extract, plays an important role in the inhibiting the plant pathogenic fungus  Alternaria alternata, and therefore its extracts can be used as low-cost fungicide with free side effects.